KINERJA PENYULUH PERTANIAN PADA KELOMPOK TANI PADI SAWAH DESA KOPIWANGKER KECAMATAN LANGOWAN BARAT - Livia ., Salu; Eyverson ., Ruauw; Vicky R.B. Moniaga (Sam Ratulangi University, 2017)
The purpose of this research is to know the performance of agriculture extension workers in wetland paddy farmer group in Kopiwangker Village, West Langowan Sub-district, Minahasa District. This research was conducted for 5 months from November 2016 until March 2017. This research uses primary data and secondary data. This research was conducted by direct interview technique, based on the prepared questionnaire to three farmer groups. They are Suka Maju Farmer Group, Esa Group and Tumou Tou farmer group. Each groups taken 3 respondents and 2 members from BP3K so total respondents are 11 people. The results showed that the level of agricultural extension performance in the farmer group in Desa Kopiwangker was quite good in relation to the seven tupoksi studied were the area potential data, the agricultural extension program, the information disseminated to the main actors, the growth of the farmer institution, the increased capacity of the main actors, Key actors of market information, technology and financing and increased production and revenue of key players.